Search for diphoton events with large missing transverse energy in 6.3fb-1 of pp̄ collisions at √s=1.96TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ancu, L. S.; et al. (American Physical Society (APS), 2010)
We report a search for diphoton events with large missing transverse energy produced in pp̄ collisions at √s=1.96TeV. The data were collected with the D0 detector at the Fermilab Tevatron Collider and correspond to 6.3fb-1 of integrated luminosity. The observed missing transverse energy distribution is well described by the standard model prediction, and 95% C.L. limits are derived on two realizations of theories beyond the standard model. In a gauge-mediated supersymmetry breaking scenario, the breaking scale Λ is excluded for Λ<124TeV. In a universal extra dimension model including gravitational decays, the compactification radius Rc is excluded for Rc-1<477GeV. © 2010 The American Physical Society.